(untitled) (Al-Aasar, 2025)
The study aimed at analyzing the extent of cognitive levels in the reading exercises of Comprehensive English Book One for Class XI using revised blooms taxonomy. It also investigated if there is a significant difference between lower order thinking skills (LOTS) and higher order thinking skills (HOTS). Additionally, the study assessed the cognitive levels of the students. The study employed a checklist and a pre- and posttest as the data collection tools, based on the revised blooms taxonomy, using a purposive sampling technique. The study adopted quantitative research design, employing action research approach to assess the students’ cognitive levels. The findings demonstrated that “Remember” (f=204, 44.54%), “Understand” (f=203, 44.32%) are the prominent levels followed by “Evaluate” (f=17, 3.71%), “Analyse (f=13, 2.84%), “Apply” (f=11, 2.40%) and “Create” (f=10, 2.18%). The results of chi-square test and fisher freeman halton test revealed a significant difference between (LOTS) and (HOTS) in the Comprehensive English Book One for Class XI. Moreover, the pre- and post-test results revealed that students’ highest improvement was demonstrated at “Evaluate” (M=3.90) followed by “Remember” (M=3.60) and “Apply” (M=3.60) levels. However, the students’ mean scores difference were moderate at “Understand” (M=3.00) and “Create” (M=2.97) levels. The lowest mean difference was recorded at Analyse (M=2.22), implying that the students exhibited limited higher order thinking skills at this level.